Experimental and computational investigation of mixing with contra-rotating, baffle-free impellers - P. Satjaritanun (2018)
© 2017 Institution of Chemical Engineers This work experimentally and numerically investigates the intersection of two fields: (1) single axis, contra-rotating impellers and (2) buoyancy of solid suspensions. The main goals of this study are to (1) create a working model to quantitatively understand particle mixing, (2) characterize and compare contra-rotating single shaft impellers to single shaft co-rotating dual impellers, (3) improve quantification of particle mixing through image processing for both computational and experimental techniques, and (4) make design decisions with the computational analysis. Twelve cases were studied by changing the direction of impeller rotation, impeller pumping direction, and the presence of baffles. Particles with specific gravities (SG) of 0.866 and 1.050 were introduced into the experimental and computational systems in a finite and countable number. The numerical solution was obtained using the Lattice Boltzmann method and the Discrete Particle method. A commercial LBM solver, XFlow, was used for the simulation. The input torques and mixing efficiency with various flow configurations and specific gravities was used to find an optimal design. For the mixing of the lighter particles, the contra configuration with inward opposing flow gave optimal performance of highest mixing efficiency at lowest required torque. Co-rotating impellers with baffles gave the best performance of high mixing efficiency at lowest power input for the heavier particles.